HIGH-STRENGTH CONCRETES WITH INTEGRATED USE OF RICE HUSK ASH, FLY ASH AND SUPERPLASTICIZERS - Nguyen Dinh Trinh Dinh Trinh (Vestnik MGSU, 2012)
The use of complex organic-mineral modifiers consisting of superplasticizers, fly ash and silicafume or rice husk ash yields high-strength concrete.